Efficacy of oversight by the legislature in Limpopo Province - Shaikh, Shahidabibi (My University, 2017)
This study examines legislative oversight practice within the Limpopo Legislature (subnational government) in South Arica, over a specific historic period. Legislative oversight and executive accountability are constitutionally mandated responsibilities. This study is focused on the fourth term (2009-2014) of the government of Limpopo, when financial management and policy implementation challenges resulted in five departments being placed under national administration. Semi-structured interviews and document analysis was utilised to understand the practice of legislative oversight and explore the challenges embedded in securing executive accountability. Drawing on the literature, a conceptual framework was used to guide the process for establishing the areas for detailed exploration. These included the legal and institutional framework for oversight; the capacity availed and utilised for oversight; and the informal institutional incentives and challenges that influenced the performance of oversight. The study revealed that oversight by the legislature and accountability by the executive are intertwined mandates and there are numerous contingencies embedded in the relationships they embody. The manner in which mandates unfold and oversight is exercised is affected by the underlying political dynamics within the dominant party. These dynamics impact on the autonomy of the legislature, shape the power relations between the executive and the legislature and creates incentives for practices that impact on legislative oversight and executive accountability. Members of the legislature were junior in party structures and did not have political authority which influenced the extent to which members of the legislature held the executive answerable as well as the extent to which the executive would account. In addition, the capacity of the institution and budget were insufficient to perform adequate oversight effectively and timeously and enable the legislature to develop into an efficient and successful institution. Furthermore, the legislature relied on the executive for information which was not always credible or reliable. This combination of factors led to oversight at times not being effective. The lessons derived from this study can be used to improve oversight effectiveness at a subnational and national governance level. However, given the role that the party plays in the governance system, there is a need for further research on party functioning, party incentives and internal democracy within the party. Key words: legislative oversight, executive accountability, parliamentary system, proportional representation, electoral system, Limpopo
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50 per cent fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management) February 2017
Keywords: Municipal finance--South Africa--Limpopo; Public administration--South Africa--Limpopo; Legislative oversight--South Africa